IN VIVO CELLULAR REPROGRAMMING FOR TISSUE REGENERATION AND AGE REVERSAL. (16th November 2018) - Lu, Y; Yu, D; Bonkowski, M; Schultz, M; Tian, X; Yang, J; He, Z; Sinclair, D
Abstract: Partial reprogramming without changing cellular identity has enormous potential to improve tissue regeneration and to reverse aspects of aging. The optic nerve injury is an excellent model for assessing the effects of age on axon regeneration in the central nervous system. In newborn rodents, optic nerves readily extend axons and regenerate after injury. In adults, however, this regenerative capacity is rapidly lost, at least partially due to epigenetic changes. Whether partial reprogramming can be achieved through an in vivo delivery approach to improve tissue regeneration is unknown. We have developed a dual adeno-associated viral (AAV) vector system allowing for the overexpression of reprogramming factors under the control of doxycycline, without any detectable leakiness. Our preliminary results showed that such AAVs are able to induce partial reprogramming safely without generating teratoma in vivo, and dramatically improve axon regeneration in adult mice. Thus, in vivo partial reprogramming through AAV delivery increases the regeneration capacity of axons after damage, and holds potential to reprogram cells in any tissue to be epigenetically younger.